2008
DOI: 10.1111/j.1365-2141.2008.07301.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐grade transformation in splenic marginal zone lymphoma with circulating villous lymphocytes: the site of transformation influences response to therapy and prognosis

Abstract: SummaryIn a series of 48 patients with splenic marginal zone lymphoma (SMZL) with circulating villous lymphocytes, we describe the clinical and laboratory features of nine cases that transformed to high-grade B-cell lymphoma. These patients had a significantly greater incidence of peripheral lymph node involvement at diagnosis when compared to SMZL patients who did not transform (P < 0AE03). While transformation in the bone marrow is frequently refractory to therapy and associated with poor outcome in SMZL, ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 13 publications
3
42
3
3
Order By: Relevance
“…Transformation to large-cell lymphoma has been documented. The incidence of this event is uncertain but may be approximately 10% [29,30]. Do we have information on the variables that have a prognostic impact regarding disease progression, transformation and/or survival?…”
Section: Which Clinical and Biological Factors Predict For Prognosis Inmentioning
confidence: 99%
“…Transformation to large-cell lymphoma has been documented. The incidence of this event is uncertain but may be approximately 10% [29,30]. Do we have information on the variables that have a prognostic impact regarding disease progression, transformation and/or survival?…”
Section: Which Clinical and Biological Factors Predict For Prognosis Inmentioning
confidence: 99%
“…However, in a minority of cases it can pursue a more aggressive course with the possibility of transformation into a diffuse large B-cell lymphoma. 3 microRNAs (miRNAs) are members of a class of small, noncoding RNAs that modulate gene expression at the posttranscriptional level in a sequence-specific manner. They have a role in controlling a variety of biological functions, including developmental patterning, cell differentiation, cell proliferation, genome rearrangements and transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The established positivity of hepatitis C virus antibodies varied from 1% [1] , which was similar to our results, to 19%, while hepatitis B virus antibodies were detected in 5% of cases [25] . Serum LDH is an important activity parameter of aggressive disease, while in low-aggressive ones, its increase can designate the transformation of disease to more severe form [18] . In our study group, this parameter was within referential limits in 72% of patients, which suggested low-grade disease status.…”
Section: A B Cmentioning
confidence: 99%
“…The frequency of mutation in the 5' non-coding region of the bcl-6 gene has been used as a marker of germinal center derivation, which might be used to establish the molecular heterogeneity [14][15][16] . Therefore, SMZL is a primary disease of the spleen, with subsequent bone marrow (BM) and peripheral blood (PB) involvement [17][18][19] . The diagnosis is based on the spleen PH, in accordance with clinical data.…”
Section: Introductionmentioning
confidence: 99%